THE DOWNTRODDEN AND THE DOWNCAST: A STUDY OF MAHASWETA DEVI’S “OUTCAST” - Mary Vijayam Alias Jinju V. J; P J, Giftlin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mahasweta Devi was an eminent Social activist who fought for the justice of the marginalised and dispossessed tribal communities in India. Her writings mainly picturizes the sufferings of women, the politics of gender, class, cast of various grounds and social relationships. Females always experience back to back trauma under male subjugation. She doesn’t pens out as a feminist but as a human being who portrays the realities behind every life. Throughout her life she expressed the plight of Indian women and raised her voices against the exploitation of women. Her works depicts the real brutality of Indian rural life. Mahasweta Devi’s Literary works became a responsible factor for the origination of historical elements to come into limelight. Her works became a pathway to put forth the downtrodden life of outcast people. The present paper will focus on depicting the life of female characters who undergone various painful circumstances under male persecution. The four stories in the Outcast presents the suppressed life of women under patriarchal system in the class and caste bounded society. In these stories she exhibits the causes lying underneath socio- political circumstances and economic exploitation of four women from the backward class and the slave trade that binds them under the democratic spell of India.